2015
DOI: 10.1164/rccm.201410-1874oc
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Channel Blocker Reduces Airway Remodeling in Severe Asthma. A Proof-of-Concept Study

Abstract: Gallopamil treatment for 12 months reduces BSM remodeling and prevents the occurrence of asthma exacerbations. Clinical trial registered with www.clinicaltrials.gov (NCT 00896428).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 26 publications
1
59
0
2
Order By: Relevance
“…Various lines of evidence in previous studies indicated that overexpression of the ADAM33 gene (mRNA and protein) was seen in various types of cells in asthma patients, including airway smooth muscle cells, fibroblasts, mesenchymal cells and endothelial cells (2)(3)(4)(5)(6). Furthermore, data from previous studies have demonstrated that the expression of the ADAM33 gene may regulate the expression of transforming growth factor-β, which is a major cytokine expressed and excreted by bronchial macrophages, epithelial cells and mesenchymal cells for airway remodeling (31). A potential mechanism by which ADAM33 affects asthma may be associated with the regulation of airway inflammation, hyperresponsiveness and remodeling processes; however, the exact molecular mechanism requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Various lines of evidence in previous studies indicated that overexpression of the ADAM33 gene (mRNA and protein) was seen in various types of cells in asthma patients, including airway smooth muscle cells, fibroblasts, mesenchymal cells and endothelial cells (2)(3)(4)(5)(6). Furthermore, data from previous studies have demonstrated that the expression of the ADAM33 gene may regulate the expression of transforming growth factor-β, which is a major cytokine expressed and excreted by bronchial macrophages, epithelial cells and mesenchymal cells for airway remodeling (31). A potential mechanism by which ADAM33 affects asthma may be associated with the regulation of airway inflammation, hyperresponsiveness and remodeling processes; however, the exact molecular mechanism requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Loss or overload of mitochondrial Fe or Ca 2+ can lead to mitochondrial dysfunction (77) and is associated with PH (76,78), NSCLC (77), asthma (78,79), and CF (33).…”
Section: +mentioning
confidence: 99%
“…Encouragingly, a recent interventional clinical trial was designed with the aim of assessing the impact of a calcium channel blocker on established airway remodelling. Specifically, the primary outcome measure was change in bronchial smooth muscle area after 12 months of treatment with the calcium channel blocker gallopamil in adults with severe asthma [77]. Treatment resulted in a reduction in bronchial smooth muscle area and in exacerbations after the intervention period.…”
Section: Airway Smooth Musclementioning
confidence: 99%